2023
DOI: 10.3389/fimmu.2023.1257072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-SARS-CoV-2 BNT162b2 mRNA vaccination on thrombin generation in children with inflammatory bowel disease

Vivien Stercel,
Linda Lóczi,
Orsolya Kadenczki
et al.

Abstract: BackgroundInflammatory bowel disease (IBD) including Crohn’s disease (CD) and ulcerative colitis (UC), are associated with higher thrombotic risk and enhanced thrombin generation (TG) in adults. Despite encouraging data reporting vaccine safety and low IBD flare rates in adults with IBD, vaccine hesitancy was demonstrated to be high in families of children with IBD. We aimed to find out whether TG is increased in children with IBD as compared to healthy controls and whether TG parameters show significant chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As soon as the rumors of the existence of an anti-SARS-CoV-2 vaccine appeared, concern was raised regarding their safety and efficiency, making parents anxious and prone to refuse to vaccinate their children [41]. However, vaccination was reported to be safe for both adults and children known to have IBD, with a low rate of vaccination-induced disease flare and a reduced risk of thrombotic events [23,[42][43][44]. Studies revealed that a third vaccine dose might be able to reduce COVID-19 incidence and lower the rates of severe outcomes, including hospital admission [45,46].…”
Section: The Impact Of Covid-19 On the Incidence Outcomes And Managem...mentioning
confidence: 99%
See 1 more Smart Citation
“…As soon as the rumors of the existence of an anti-SARS-CoV-2 vaccine appeared, concern was raised regarding their safety and efficiency, making parents anxious and prone to refuse to vaccinate their children [41]. However, vaccination was reported to be safe for both adults and children known to have IBD, with a low rate of vaccination-induced disease flare and a reduced risk of thrombotic events [23,[42][43][44]. Studies revealed that a third vaccine dose might be able to reduce COVID-19 incidence and lower the rates of severe outcomes, including hospital admission [45,46].…”
Section: The Impact Of Covid-19 On the Incidence Outcomes And Managem...mentioning
confidence: 99%
“…Schell and colleagues reported that IBD patients on biologics are susceptible to reinfection because of their weakened IgG response to natural SARS-CoV-2 infection [33]. Furthermore, one-third of the patients under anti-TNF alpha therapy, failed to maintain high post-vaccination anti-SARS-CoV-2 IgG/IgM levels [42,47,48]. However, following vaccination, the antibody response is much higher than to natural infection, offering additional protection against a possible SARS-CoV-2 infection [13].…”
Section: The Impact Of Covid-19 On the Incidence Outcomes And Managem...mentioning
confidence: 99%